Varieties of Transportation Justice: U.S. Transportation Equity Policy and the Civil Rights Movement. Issue 1 (January 2015) - Gordon, Cameron
Transportation policy has long been concerned with the achievement of direct outcomes (e.g., maximum mobility, reduced unit travel times, increased access) and with indirect outcomes (e.g., regional economic development). More recently, a distinct concern has arisen about equity and justice in transportation and, in a broad sense, about whether all transport system users have equal access and fair burden and benefit distributions. The equity policy framework in the United States rests on and is closely bound up with the post–Civil War struggle for civil rights. This paper (a) describes what American conceptions of civil rights have come to mean in U.S. policy and legal spheres, (b) discusses the extent to which transportation is seen as a civil right, (c) discusses what the limits of those rights are and how those definitions have changed over time, and (d) suggests some current issues for U.S. policy makers that, going forward, must be considered in a civil rights approach to transportation equity.